Anunciou: vendeu???? O anúncio publicitário na mídia impressa e os mecanismos de sua construção como gênero: uma análise funcional-discursiva - Rosane Cassia Santos Campos (2012)
This thesis is an inquiry into advertisements written in Portuguese and issued in Brazilian magazines. We work along the hypothesis that advertisements constitute a legitimate textual gender, with its own characteristics and bearing specificities as to its production. This study is founded on the theory of Multimodality in terms of the Visual Design Grammar as proposed by Kress and Van Leeuwen (2006). Theyconsider the text from a visual / verbal point of view, by assuming that various semiotic modes serve certain communication purposes. This study is also based on Mann and Thompsons (1988) Rhetoric Structure Theory (RST). This is a descriptive theory whose object of investigation is explicit and implicit relations among text parts. We describe the emergence of so called rhetoric relations, or relational propositions or coherence relations. An intersection of both theories is proposed, revealing a possible interface between Functionalism and Textual Linguistics. Thus we point to the fact that visual and verbal considerations may clarify the argumentative force of this genre as to its persuasive power. Moreover, we reflect upon the main focusing resources in advertisements, emphasizing their importance for the interaction between advert producer and prospective readers. The corpus contains thirty-one advertisements in written. They were randomly selected regarding theme and intended audience. We believe advertisements to be a textual genre of wide social circulation. Data analysis reveals that the nucleus/satellite rhetoric relation of Elaboration is the most frequent and that the multimode aspects regarding Given/New; Ideal/Real; Margin/Center go through changes. The significant presence of the nucleus/satellite relation of Elaboration can be justified when we consider thatthe informational content of advertisements requires extra details that could add value to the product, idea or service being commercialized.